Localization microscopy (SPDM) reveals clustered formations of P-glycoprotein in a human blood-brain barrier model - Huber, Olga; Brunner, Alexander; Maier, Patrick; Kaufmann, Rainer; Cremer, Christoph; Fricker, Gert (PLOS ONE, 2012)
P-glycoprotein (Pgp; also known as MDR1, ABCB1) is the most important and best studied efflux transporter at the blood-brain barrier (BBB); however, the organization of Pgp is unknown. The aim of this study was to employ the recently developed super-resolution fluorescence microscopy method spectral precision distance microscopy/spectral position determination microscopy (SPDM) to investigate the spatial distribution of Pgp in the luminal plasma membrane of brain capillary endothelial cells. Potential disturbing effects of cell membrane curvatures on the distribution analysis are addressed with computer simulations. Immortalized human cerebral microvascular endothelial cells (hCMEC/D3) served as a model of human BBB. hCMEC/D3 cells were transduced with a Pgp-green fluorescent protein (GFP) fusion protein incorporated in a lentivirus-derived vector. The expression and localization of the Pgp-GFP fusion protein was visualized by SPDM. The limited resolution of SPDM in the z-direction leads to a projection during the imaging process affecting the appeared spatial distribution of fluorescence molecules in the super-resolution images. Therefore, simulations of molecule distributions on differently curved cell membranes were performed and their projected spatial distribution was investigated. Function of the fusion protein was confirmed by FACS analysis after incubation of cells with the fluorescent probe eFluxx-ID Gold in absence and presence of verapamil. More than 112,000 single Pgp-GFP molecules (corresponding to approximately 5,600 Pgp-GFP molecules per cell) were detected by SPDM with an averaged spatial resolution of approximately 40 nm in hCMEC/D3 cells. We found that Pgp-GFP is distributed in clustered formations in hCMEC/D3 cells while the influence of present random cell membrane curvatures can be excluded based on the simulation results. Individual formations are distributed randomly over the cell membrane.